PREVENTING STUNTING THROUGH ASSISTANCE FOR PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY - Umami, Riza; Restanty, Dian Aby (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
: Stunting is dwarfism or short stature characterized by growth failure in children under five years of age (toddlers) due to chronic malnutrition and repeated infections, especially during the first 1,000 days of life (HPK), from the fetus to 23 months of age. A child is classified as stunted if their length or height is below minus two standard deviations of the length or height of children of the same age. The purpose of this activity is to provide assistance to pregnant women with KEK in an effort to prevent stunting using appropriate and sustainable methods. According to SKI in 2023, the prevalence of stunting in Jember is 29.7 percent. In March 2023, the number of stunted toddlers at the Mangli Community Health Center was 18.97% or 294 toddlers, making the Mangli Community Health Center the second highest in terms of stunting cases in Jember Regency. Assistance activities for pregnant women with KEK showed that most respondents were malnourished and had limited understanding of the impact of KEK. After the intervention, there was an increase in knowledge levels (from 30% to 60%), a decrease in anemia (from 53% to 37%), and an increase in the regularity of iron tablet consumption (from 77% to 87%). This support program can be continued with a focus on practical nutrition education, routine monitoring of pregnant women’s status, and family involvement in supporting nutritional fulfillment for stunting prevention. Keywords: stunting, pregnant women with chronic energy deficiency